Challenges and Strategies in Crude Palm Oil Quality Control: A Practical Approach from an Indonesian Palm Oil Mill - Syarifatul Ulum; Siti Nursyamsiah (UNIVED Press, 2026)
This study analyzes the implementation of the Crude Palm Oil (CPO) quality control system at an Indonesian palm oil mill, focusing on procedures, methods, and technologies used, as well as the challenges in maintaining product quality according to company standards. A qualitative approach was employed, utilizing participatory observation, in-depth interviews, and document analysis. Data were analyzed thematically and through Juran’s Trilogy framework, encompassing quality planning, quality control, and quality improvement. The quality control system involves the implementation of Standard Operating Procedures (SOPs), manual sorting, Statistical Quality Control (SQC), manual testing, Foss NIRS technology, and data reporting via paper-based forms, WhatsApp, Excel, SAP, and the WD application. Identified challenges include inconsistent adherence to SOPs, delayed reporting, limited technological use, and weak interdepartmental coordination. The analysis indicates that while quality planning and control are adequately implemented, quality improvement remains suboptimal. Recommendations include staff training, SOP simplification, real-time reporting systems, enhanced cross-divisional coordination, and supplier development. Gradual implementation of these strategies is expected to enhance system effectiveness and support long-term sustainability.